Driving with love: As an effective leadership style that achieves job satisfaction for subordinates (Journal of Economic Additions, 2020)
This study aimed to shed light on love leadership (parenting leadership) or as it is called maternal leadership as an effective leadership style, and an attempt to demonstrate its role in improving the job satisfaction of the subordinates, by extrapolating and analyzing many related studies. finally, the study concluded that love is an effective leadership method to achieve job satisfaction, when the worker feels the love of his leader, and sees situations and behaviors that reveal love, he offers love, loyalty, cooperation and sacrifice.The study recommended that the leader always work to build a work environment free from routine and close to interaction and harmony, Because job satisfaction for employees is one of the fruits of love, not rigid systems, hollow structures, administrative procedures, or sanctions regulations.Keywords: Driving with love, Job satisfaction, Parental leadership, Driving by maternity instinct.Jel Classification Codes: J28، M54.